THE IMPLEMENTATION OF PAYROLL ACCOUNTING SYSTEM AS AN EFFORT TO IMPROVE THE SYSTEM OF INTERNAL CONTROL (A Study at PDAM Kota Malang) - Fio Alfiandi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2014)
This research aims to determine the implementation of payroll accounting system in PDAM Kota Malang as an effort to improve the internal control system and to provide the alternative problem solving if obstacles related to the system exists. Using descriptive method, the researcher obtained relevant data by using interview and documentation. The result shows that the system is well-implemented and it supports the internal control. It is evidenced by the involvement of related functions in the processing the payroll effectively. Also, the authorization of every job is clear and following the procedure. This study suggests the company to add more specific information related to income tax discounted from the employees’ take home pays. This research also recommends the company to apply more complete flowchart of payroll system. Key Words: Payroll Accounting System, Internal Control ABSTRAK Penelitian ini bertujuan untuk mengetahui penerapan sistem akuntansi penggajian di PDAM Kota Malang sebagai upaya untuk meningkatkan sistem pengendalian internal dan memberikan alternatif pemecahan masalah jika hambatan yang berkaitan dengan sistem ada. Dengan menggunakan metode deskriptif, peneliti memperoleh data yang relevan dengan menggunakan metode wawancara dan dokumentasi. Hasilnya menunjukkan bahwa sistem ini diimplementasikan baik dan mendukung pengendalian internal. Hal ini dibuktikan dengan keterlibatan fungsi-fungsi terkait dalam pengolahan penggajian secara efektif. Juga, otorisasi setiap pekerjaan jelas dan mengikuti prosedur. Studi ini menunjukkan perusahaan untuk menambahkan informasi yang lebih spesifik terkait dengan potongan pajak penghasilan dari upah bersih karyawan. Penelitian ini juga merekomendasikan perusahaan untuk menerapkan flowchart lebih lengkap dalam sistem penggajian. Kata Kunci: Sistem Akuntansi Penggajian, Pengendalian Intern